The limited liability company. - Jelsma, Phillip L., 1958-; Nollkamper, Pamela Everett (James Publishers, 2014)
Model formation and operation documents, drafting tips, sample client letters, comparison charts, IRS revenue rulings and more. The authors discuss each state act separately in a detailed state-by-state analysis that includes checklists and forms. -- from publisher's web site.